Pattern Of Hand Injuries in a Teaching Hospital of a Developing Country - Shrestha, Kishor Man; Pandey, A; Shrestha, B (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Hand injuries are common and are responsible for a significant hospital emergency visit and most of which are seen by non hand specialists. The pattern of the injuries varies from place to place. It is pertinent that those who may come across the patients understand this pattern. MATERIALS & METHODS: A retrospective review of records of patients presenting with hand injuries to the emergency unit and in OPD unit over two year period was carried out highlighting the pattern of the injury. RESULTS: The common cause of hand injury in these patients was fodder cutter machines which is 53 patients (30.6%) followed by industrial machines injury in 36 patients (20.8%), road traffic accidents in 30 patients (17.3%), physical assault in 19 patients (10.9%), threshing machines in 13 patients (7.5%), fall in 9 patients (5.2%), falling objects in 8 patients (4.6%), door injury in 2 patients (1.15%) and sports injury in 1 patient (0.5%). The injury was more common in young adults between 15 to 34 years of age with the mean age of 24.5 years. Most of the injury occurred during work by fodder cutter machine and industrial machines or other causes as road traffic accidents. In the present study, 17.3% cases had injury on Saturday comprising 80.9% of males and 53.1% of cases had fractures with high incidence of injury of the Right hand which was 53.7%. Most of the cases having fractures were of Gustilo II variety (28.2%) and 94.2% of cases were of minor to moderate grades of severity of hand injury on grading by HISS grading. CONCLUSION: Understanding the pattern of injury can impart positively on the management of hand injuries and for its preventive measures. Journal of Universal College of Medical Sciences (2017) Vol.05 No.01 Issue 15, page: 29-32